Highly enhanced transport by supersonic N-crowdions - Dmitriev, Sergey V. (2020)
An interstitial atom placed in a close‐packed atomic row of a crystal is called crowdion. Such defects are highly mobile, they can move along the row transporting mass and energy. In the present study the concept of the classical supersonic crowdion is generalized to N ‐crowdion in which not one but N atoms move simultaneously at a high speed. With the help of molecular dynamics simulations for fcc Morse crystal it is demonstrated that N ‐crowdions are much more efficient in mass transport being able to propagate through larger distances having smaller total energy than the classical 1‐crowdion.